Ethnoagriculture and Food Sovereignty in Kampung Cireundeu: An Environmental Education Perspective - Miranto, Sujiyo; Arif, Muhamad; Zulfiani, Zulfiani; Anwar, Chairul (Universitas Islam Negeri Raden Intan Lampung, 2025)
The people of Kampung Cireundeu have preserved a unique ethnoagricultural tradition centered on cassava cultivation, which plays a vital role in sustaining their food sovereignty and security. This study aims to explore how this tradition reflects principles of environmental education. Employing an ethnographic approach, data were collected through observation, in-depth interviews, and documentation. The findings reveal five key traditions passed down across generations. First, the community practices land management by dividing fields into multiple plots planted sustainably using intercropping, ensuring continuous food surplus. Second, they implement fallow periods (Bera) to restore soil fertility. Third, sheep are raised alongside crops, providing economic support. Fourth, cassava is processed into Beras Singkong (Rasi) as a rice substitute. Fifth, Rasi is creatively transformed into a variety of daily meals. These interrelated practices illustrate how local knowledge and ecological wisdom contribute to both food sovereignty and environmental sustainability. Furthermore, the community’s ethnoagricultural system serves as a rich educational model for promoting environmental awareness and sustainable living. The study underscores the importance of integrating indigenous agricultural practices into environmental education frameworks to support resilient food systems.